Guide to legal career : understanding the options, the advantages and the challenges - Zul Kepli, Mohd Yazid (PST Enterprise, 2011)
Written for law students and lawyers, this book is virtual encyclopaedia for those in transition, covering such topics as legal career options, how to conduct a self-assessment and transferable skills analysis, how to market special talents, how to decide whether to stay in law or leave and how to avoid job-interview hell.